A matrix of morphology and distribution of calcifications in the breast: Analysis of 849 vacuum-assisted biopsies. Issue 86 (January 2017) - Kaltenbach, Benjamin; Brandenbusch, Volker; Möbus, Volker; Mall, Gerhard; Falk, Stephan; van den Bergh, Marcus; Chevalier, Frauke; Müller-Schimpfle, Markus
Highlights: A diagnostic matrix of morphologies and distributions of calcifications enables their standardized classification into BI-RADS categories. 285/328/208/29 groups of calcifications were prospectively classified as BI-RADS 4A/4B/4C/5 correlating with a risk for malignancy of 16%/27%/55%/90%. Overall, 275/849 (32%) groups of calcifications were found to be malignant. Abstract: Objective: The purpose of this retrospective analysis was to evaluate the likelihood of malignancy in prospectively categorized BI-RADS 4 and BI-RADS 5 calcifications. Material and methods: This analysis included 849 women who underwent vacuum biopsy for BI-RADS 4 (with the subgroups 4A, 4B and 4C) or BI-RADS 5 calcifications between February 2007 and May 2015. Calcifications were classified according to the morphology and distribution descriptors of the BI-RADS lexicon (BI-RADS 4th edition lexicon). A standardized scheme (matrix) was used to combine the characteristics of the grouped calcifications with the BI-RADS assessment category. Results: Overall, 275/849 (32%) lesions were found to be malignant. 285/327/208/29 calcified lesions were prospectively classified as BI-RADS 4A/4B/4C/5 indicating a risk for malignancy of 16%/27%/55%/90%, respectively. The morphology descriptors predicted the risk for malignancy as follows: typically benign (n = 55): 2%; indeterminate (n = 676): 27%; typically malignant (n = 118): 80%. The distribution descriptors correlated with a malignant histology as follows: diffuse (n = 0); round or oval (n = 261): 22%; regional (n = 398): 33%; segmental (n = 106): 42%; linear or branching (n = 85): 55%. There was a significant difference between the descriptor categories (p < 0.0001). Conclusion: A standard scheme combining the morphology and distribution characteristics proved to be a helpful tool in diagnosis of calcifications, bridging the gap between description and classification of these lesions.